The release of light metals from a brown seaweed (Sargassum sp.) during zinc biosorption in a continuous system - da Costa, Antonio Carlos Augusto; Mora Tavares, Ana Paula; Pessôa de França, Francisca (Electronic Journal of Biotechnology, 2001)
The biosorption of zinc and calcium was investigated with a biomass of Sargassum sp., a brown seaweed, in a continuous system consisting of three serial tubular fixed-bed laboratory reactors. Results indicated that zinc was efficiently recovered by the biomass. After treatment of 9.0 liters of a mixed solution containing 130.0 mg/l zinc and 260.0 mg/l calcium, the first column of the system saturated with zinc; the remaining columns did not saturate with zinc as a result of the pre treatment performed by the first reactor. Calcium was also efficiently biosorbed by the biomass, saturating the system much faster than zinc. X-ray fluorescence spectrum indicated the presence of various elements in the structure of the Sargassum sp. biomass, especially alkaline and alkaline-earth elements. Alkaline and alkaline earth elements played a key role in the biosorption of zinc, being responsible for ion-exchange reactions performed during zinc biosorption.